Trade Facilitation Provisions in Preferential Trade Agreements : Impact on Peru’s Exporters - Lee, Woori; Rocha, Nadia; Ruta, Michele (World Bank, Washington, DC, 2021)
Trade facilitation measures that simplify, modernize, and harmonize export and import processes are particularly important in a world of global value chains where goods cross borders multiple times. At the firm level, trade facilitation commitments in preferential trade agreements can generate larger gains for firms participating in global value chains, as these firms can benefit both from efficiency enhancement at their own border (when importing inputs) and at the partner countries’ borders (when exporting). This paper uses Peruvian customs data to investigate the heterogeneous impact of trade facilitation provisions across firms, depending on their global value chain linkages. The results show that trade facilitation provisions in preferential trade agreements promote the export performance of global value chain firms, especially when they import inputs from the preferential trade agreement partner country. In the case of Peru, the main benefit of trade facilitation provisions results from efficiency enhancements at its own border, allowing global value chain firms to import inputs in a more timely and predictable manner.